2017
DOI: 10.1038/nature21417
|View full text |Cite
|
Sign up to set email alerts
|

Root microbiota drive direct integration of phosphate stress and immunity

Abstract: Plants live in biogeochemically diverse soils that harbor extraordinarily diverse microbiota. Plant organs associate intimately with a subset of these microbes; this community’s structure can be altered by soil nutrient content. Plant-associated microbes can compete with the plant and with each other for nutrients; they can also provide traits that increase plant productivity. It is unknown how the plant immune system coordinates microbial recognition with nutritional cues during microbiome assembly. We establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
604
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 718 publications
(686 citation statements)
references
References 52 publications
36
604
2
6
Order By: Relevance
“…During infection of SAP11 AYWB Arabidopsis plants with the bacterial pathogen Pseudomonas syringae , the induction of defence responses was suppressed and the SAP11 AYWB plants exhibited susceptibility to bacterial infection (Lu et al , ). In other studies, cross‐talk between Pi starvation and salt and drought stress signalling pathways, or hormone‐signalling pathways, has been described (Song and Liu, ; Abbas Khan et al ., ; Baek et al , ; Castrillo et al , ). Knowing that the defence‐related hormones JA and ethylene (ET) function as signalling hormones in the rice defence against M. oryzae (Nasir et al , ), a major future challenge is to determine whether Pi content affects defence hormone signalling in rice for the control of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…During infection of SAP11 AYWB Arabidopsis plants with the bacterial pathogen Pseudomonas syringae , the induction of defence responses was suppressed and the SAP11 AYWB plants exhibited susceptibility to bacterial infection (Lu et al , ). In other studies, cross‐talk between Pi starvation and salt and drought stress signalling pathways, or hormone‐signalling pathways, has been described (Song and Liu, ; Abbas Khan et al ., ; Baek et al , ; Castrillo et al , ). Knowing that the defence‐related hormones JA and ethylene (ET) function as signalling hormones in the rice defence against M. oryzae (Nasir et al , ), a major future challenge is to determine whether Pi content affects defence hormone signalling in rice for the control of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, P sufficiency has been associated with increased defense gene expression in roots. This was shown to be responsible for changes in a synthetic bacterial rhizosphere and root community (Castrillo et al ., ) and suppression of the endophytic fungus Colletotrichum tofieldiae , which delivers P under LP conditions (Hacquard et al ., ; Hiruma et al ., ). We hypothesize that P‐induced defense responses in lateral roots could also be responsible for the fungal community shifts observed in field‐grown maize roots grown at HP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using both wild soil and a synthetic bacterial community demonstrated that Arabidopsis PSR mutants assemble a different root microbiome than wild type plants, even when grown in phosphate-sufficient soil. Further, the master transcriptional regulator of PSR directly integrates this nutritional stress response and immune system outputs [97]. These early examples suggest that the coordination of defense and nutrition is critical to driving microbiome function.…”
Section: Genetic Control Of Beneficial Plant-microbe Interactionsmentioning
confidence: 99%
“…Purple: Firmicutes, Blue: Actinobacteria, Yellow: Bacteroidetes, Pink: Deinococcus-thermus and Orange: Proteobacteria. The tree was constructed using a concatenated filtered alignment of 31 single copy genes [97]. The genome assemblies of each of the three different sequencing projects can be accessed via the IMG/JGI portal by using the following project IDs:…”
Section: Figurementioning
confidence: 99%